Internalizing/Externalizing Problems and Sensory Processing Alteration in Children Referred to Child Mental Health Centers - Macarena Valencia; Ana D’Ocon; Raquel Plata; Sandra Simó; María José Cantero (Children)
Background/Objectives: Internalizing and externalizing problems have been associated with sensory processing (SP) alteration, where severe alterations are equivalent to sensory processing disorder (SPD). This study aims to examine the relationship between childhood problems and the degree of SP alteration in children referred to a child mental health center (CMHC). Methods: The study included sixty-four children (44 boys and 20 girls), aged 6 to 8 years, referred to a CMHC in Gipuzkoa, Spain. Parents completed the Child Behavior Checklist (CBCL/6–18) and the Child Sensory Profile (CSP-2). Analyses of variance and qualitative analyses were conducted to compare T-scores of childhood problems across SP alteration groups (no alteration, mild, moderate, and severe). Results: Of the participants, 31.3% (n = 20) exhibited a severe SP alteration and obtained significantly higher scores than those without SP alteration on the Withdrawn/Depressed and Attention, Social, and Thought Problems syndrome scales, as well as on the Internalizing Problems and Total Problems scales. Furthermore, children with severe SP alteration scored within the clinical range on the Anxious/Depressed and Attention Problems scales. Mean scores for Internalizing, Externalizing and Total Problems reached the clinical threshold when the SP alteration was classified as moderate or severe. These findings indicate that SP alteration is associated with increased internalizing and externalizing problems in children referred to the CMHC, with clinical levels observed particularly in cases of moderate to severe SP alteration. Conclusions: This study highlights the importance of including SP assessment in the diagnostic evaluation of childhood mental health problems.